(untitled) (Praxis Educativa, 2020)
The study of the transition to university attempts to provide insights into the increase in school failure during the first year of university. Transition is problematized as a standardized phenomenon that ignores students’ irregular literate trajectories. This study aims to contrast academic and non-academic literate practices to account for the process of appropriation of literate culture in transition, its disruptions and emerging literate identities. A qualitative descriptive study is proposed, with a phenomenological approach to account for hierarchically structured categories of description. It is based on two series of focus groups (70 students) and eight interviews. The most relevant results indicate that literate practices coexist with the deficit discourse. The need to value reading identities from vernacular contexts and at the same time provide progressive access to dominant forms of literate practice is considered.